Respostas

A melhor resposta!
2014-01-14T23:02:17-02:00
Calcule:

a) (-4a) + (2a) 
    -4a+2a= -2

b) (2x-3b)+(-5x+4b)
      2x-3b-5x+4b
      2x-5x-3b+4b
      -3x+b

c) (4am²)-(-3am²)
     4am²+3am²= 7am²

d) (-10xy)+(8²xy)+(-7²xy)+13xy
     -10xy+8²xy-7²xy+13xy
     -10xy+64xy+49xy+13xy
      -10xy+126xy= 116 xy
      
    
1 5 1
2014-01-14T23:09:23-02:00
a) (-4a) + (2a)
  -4a + 2a = -2a

b) (2x-3b)+(-5x+4b) =  -3x + b

c) (4am²)-(-3am²) =7am²

d) (-10xy)+(8²xy)+(-7²xy)+13xy
  -10xy + 64xy +(49xy) + 13xy = 116xy